English aristocratic women's religious patronage, 1450-1550: the fabric of piety - Harris, Barbara J. (Gendering the Late Medieval and Early Modern World, 2018)
The role played by women in the evolution of religious art and architecture has been largely neglected. This study of upper-class women in the fifteenth and sixteenth centuries corrects that oversight, uncovering the active role they undertook in choosing designs, materials, and locations for monuments, commissioning repairs and additions to many parish churches, chantry chapels, and almshouses characteristic of the English countryside. Their preferred art, Barbara Harris shows, reveals their responses to the religious revolution and signifies their preferred identities.